Performativitas Gender dalam Hikajat Njonja Kam Giok Nio (1925): Analisis Teori Judith Butler - Muhammad Abiel Miladz; Susan Permadini (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This article aims to analyze Sie Hian Ling's Hikajat Njonja Kam Giok Nio (1925) through Judith Butler's theory of gender performivity in order to uncover the mechanism of gender regulation in the colonial context of the Dutch East Indies. The narrative tells the social destruction of Njonja Kam Giok Nio, the wife of a Chinese Luitenant in Tjibingin, who loses her status, family, and dignity due to her involvement with Stamboel comedy actor Siek Ting San. The analysis shows that text functions as a discursive regulatory apparatus that constructs gender as a performance that must be repeated through signs of modesty, chastity, and marital status, rather than innate identity. With the concepts of iteration, desire-performattity, radical transgression, abjection, and normative re-iteration, this article reveals how colonial moralistic narratives maintain heteronormativity through the threat of systematic social destruction. Njonja Kam Jade Nio, who originally succeeded in the performance of honorable femininity, experienced gender un-doing when entering public spaces without supervision, became an active desire agent, and was in contact with lower-class subjects. The consequence is total abjection in the form of physical expulsion, renaming, economic exclusion, and intervention by the colonial apparatus. The results of the study confirm that gender analysis cannot be separated from colonialism and class as a system of power that produces each other in the historical context of the Dutch East Indies in the 1920s.